Contribution of parental support and learning discipline to science learning outcomes of grade V elementary students - Fajar Ashwary; Sintha Sih Dewanti; Amanda Listiani (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
The present study analyses the contribution of learning discipline and parental support to the learning outcomes of Natural Sciences (IPA) of grade V elementary students. The study used a quantitative approach with an associative correlational design involving 60 grade V students of SDN 1 Banda Sakti in Lhokseumawe. Data were collected through questionnaires and analysed using multiple linear regression with the help of SPSS. The results revealed that learning discipline and parental support had a significant effect on science learning outcomes, both simultaneously (F = 42.668; p < 0.05) and partially. An R² value of 0.600 indicates that the two variables together explain 60% of the variation in students' science learning outcomes. Regression coefficient analysis also revealed that learning discipline had a more dominant influence (β = 0.576; t = 6.836; p < 0.05) compared to parental support (β = 0.465; t = 5.516; p < 0.05). These findings confirm that strengthening learning discipline needs to be the main focus of educational interventions, in addition to increasing school-family collaboration in creating a learning environment that supports students' academic success.